Microstructure modification of 3D printed aluminium alloys by friction stir processing - Du, Zheng Lin (2022)
Friction stir processing is a solid-state welding technology capable of joining metal parts without the melting. The microstructure of the material evolved during the process vary from columnar grain along the thermal gradient in the melt pool to fine equiaxed grains. Evaluation on its mechanical properties in terms of micro-hardness was performed. A significant decrease in microhardness was observed in the processed region. The decrease in the microhardness is mainly attributed to the dissolution of hardening precipitates in the aluminium matrix.